“Narimo ing Pandum”: How Highlander Women Perceive Poverty as a Destiny in Gunungkidul, Yogyakarta - Jati, Wasisto Raharjo (UI Scholars Hub, 2023)
The Javanese proverb “narimo ing pandum”exemplifies a belief among poor people to accept their impoverishment as the Divine will of God. This belief, however, has the adverse effect of habituating people to accept poverty. Such perception is conditioned, among others, by the availability of state-provided social aid as well as family or community support, which has helped the poor to stay afloat in moments of crises. In a patriarchal society, poverty poses even more risks and challenges for women, who are often conditioned to be reliant on men to survive. As such, poor women are likely required to find ways to cope with their helplessness. This article seeks to contribute to discussions on the cultural properties of poverty by exploring aspects of gender inequality. Specifically, it discusses how highlander women in Gunungkidul, the region with the highest poverty rate in Yogyakarta, perceive their impoverishment as Divine date, and explores how their perception of poverty affects their survival. The method utilized is a Life History Approach, which captures the multiple facets of our subjects by analyzing their day-to-day activities and interactions.